1990
DOI: 10.1016/0169-4332(90)90018-u
|View full text |Cite
|
Sign up to set email alerts
|

Angle-resolved X-ray photoelectron spectroscopy (ARXPS) and a modified Levenberg-Marquardt fit procedure: a new combination for modeling thin layers

Abstract: The combination of angle-resolved X-ray photoelectron spectroscopy (ARXPS) and a modified Levenberg-Marquardt (LM) fit procedure has been used to study a native oxide layer on a clean Si(100) substrate. Numerical calculations show that with an aperture of 3 o or 9 o of the electron analyser, the photoelectron takeoff angle should not exceed 80 o or 70 o, respectively, as compared to normal takeoff angles. At larger photoelectron takeoff angles, the effect of the aperture on the photoelectron energy distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(63 citation statements)
references
References 24 publications
5
54
2
Order By: Relevance
“…The measured function G(a) was close to that obtained on a clean sputtered Si sample [15]. The thickness of the contamination layer on the sheet and the single crystal of tungsten has been measured.…”
Section: Arx P S Measurementsmentioning
confidence: 51%
See 3 more Smart Citations
“…The measured function G(a) was close to that obtained on a clean sputtered Si sample [15]. The thickness of the contamination layer on the sheet and the single crystal of tungsten has been measured.…”
Section: Arx P S Measurementsmentioning
confidence: 51%
“…In this method the same XPS peak is measured at varying photoelectron take-off angle and its intensity is normalized to the normal take-off angle. For the intensity of the XPS peak of tungsten, measured at different electron take-off angles (00 and normalized to its intensity at normal take-off angle (0t = 0), we may write [15]:…”
Section: Arx P S Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…With a model we proposed earlier, we showed that ARXPS experiments enable us to determine the thickness of a surface layer with great accuracy [21]. In this report in section 2, we improve this model so that it can be used for the quantitative analy:is of ARXPS spectra, taken on c-axis oriented high-To 0169-4332/92/$05.…”
Section: Introductionmentioning
confidence: 99%